Substituted Bi3.5Mg1.8Nb2.7O13.8 pyrochlores with transition metals (Zn, Ni and Cd): doping mechanism, structure and electrical properties - Tan, Phei Yi; Tan, Kar Ban; Khaw, Chwin Chieh; Murthy, H.C. Ananda; Balachandran, Ruthramurthy; Chen, Soo Kien; Lee, Oon Jew; Chan, Kah Yoong; Lu, Ming (University of Novi Sad, Faculty of Technology, 2024)
The influence of transition metals (Zn, Cd and Ni) on bismuth magnesium niobate (Bi3.5Mg1.8Nb2.7O13.8, BMN) pyrochlores was investigated. Considering the difference in their ionic radii, Cd was postulated to substitute Mg at the eight-fold coordinated A-site whereas Zn and Ni were to replace Mg at the six-fold coordinated B-sites of the host structure. Solubility limits in these substitutional pyrochlore solid solutions were determined to be 0.4, 0.1 and 0.3 for Zn, Ni and Cd, respectively. Upon introducing these divalent cation dopants, notable changes in the lattice parameters and grain sizes were observed with increasing dopant concentration. The high dielectric constants, ε′ of Zn, Cd and Ni doped BMN pyrochlores were discernible with their bulk values of 195–216, 173–195 and 153–195, respectively. The highest ε′ of 216 was recorded for the composition with Zn = 0.1 in contrast to the lowest value of 153 found in the composition with Ni = 0.1. Meanwhile, these highly insulating divalent cation doped BMN pyrochlores also exhibit low dielectric losses, tan δ whose values are in the order of 10−3. The excellent dielectric properties allow these novel pyrochlore phases to be potentially applied for the energy storage applications.